(untitled) (Bodhi Path, 2021)
Buddhism is an Indian born religion based on the guidelines of Gautam Buddha began around the sixth century, B.C.E. and has influenced the civilization of mostly Asian countries over the past 2500 years. Since the Buddhism is Indian origin religion but due to various factors and with the passage of time it disappeared from the Indian land. The back to back three attacks on the Nalanda University and other Buddha viharas like Vikramasila and Odantapuri, whereas first attacked by the Huns (455-467), second by Gaudas in early 7th century and third by Muslim Army led by Turkish leader Bakhtiyar Khilji in 1193 A.D which was a great setback for Buddhism. The attack by Khilji lead to huge destruction including death of thousand of monks, intellectuals, scholars and students, demolition of Buddhist infrastructure, Buddhist literature and more than 10 million manuscriptswhich was written thousands and thousands of years ago. The attack on Nalanda University led by Bakhtiyar Khilji in 1193 A.D uprooted of Buddhist base of learning from the Indian main land and shifting the Buddhist knowledge towards the northern-eastern part of India and abroad. Since then many attempts did so far in the history of India by various Buddhist rulers, intellectuals and Buddhist monks for the revival of Buddhism in the mother land in its original form. The paper establishes a co-relation between the constitution of India and Buddhism and the implications of Buddhist thoughts in the modern society for its welfare on many grounds. The Buddha throughout his life taught the path of truth and focused to equalize the unequal society by delivering teachings on the idea of co-operation, non-violence, humanity, kindness compassion and peace. These approaches are also inherited by many nations of modern world like China, Nepal, Tibet, Mongolia and other Buddhist countries for their smooth functioning. Also the Buddha established institution- The Sangha, was first of its kind which was based on people’s participation and democratic pattern and norms. These democratic norms of Buddhism are the essential ingredient of the constitution of India. The framers of the constitution of India adopt these democratic values from the Buddhism in order to establish a nation where an individual can live with dignity and peace. Just like Buddhism, the Constitution of India gives the supreme power to the people of this country to administer along with a long list of justifiable rights which gives freedom, equality and justice. While this research paper is related to find out the main elements of Buddhism, its thoughts, approaches, their justifications and implications in the constitution of India. Lastly we will also try to study/focus the reflection of Buddhism on the constitution of India in the full paper.